Night workers with circadian misalignment are susceptible to alcohol-induced intestinal hyperpermeability with social drinking - Swanson, Garth R.; Gorenz, Annika; Shaikh, Maliha; Desai, Vishal; Kaminsky, Thomas; Van Den Berg, Jolice; Murphy, Terrence; Raeisi, Shohreh; Fogg, Louis; Vitaterna, Martha Hotz; Forsyth, Christopher; Turek, Fred; et al. (American journal of physiology: Gastrointestinal and liver physiology, 2016)
Alcohol-induced intestinal hyperpermeability (AIHP) is a known risk factor for alcoholic liver disease (ALD), but only 20–30% of heavy alcoholics develop AIHP and ALD. The hypothesis of this study is that circadian misalignment would promote AIHP. We studied two groups of healthy subjects on a stable work schedule for 3 mo [day workers (DW) and night workers (NW)]. Subjects underwent two circadian phase assessments with sugar challenge to access intestinal permeability between which they drank 0.5 g/kg alcohol daily for 7 days. Sleep architecture by actigraphy did not differ at baseline or after alcohol between either group. After alcohol, the dim light melatonin onset (DLMO) in the DW group did not change significantly, but in the NW group there was a significant 2-h phase delay. Both the NW and DW groups had no change in small bowel permeability with alcohol, but only in the NW group was there an increase in colonic and whole gut permeability. A lower area under the curve of melatonin inversely correlated with increased colonic permeability. Alcohol also altered peripheral clock gene amplitude of peripheral blood mononuclear cells in CLOCK, BMAL, PER1, CRY1, and CRY2 in both groups, and inflammatory markers lipopolysaccharide-binding protein, LPS, and IL-6 had an elevated mesor at baseline in NW vs. DW and became arrhythmic with alcohol consumption. Together, our data suggest that central circadian misalignment is a previously unappreciated risk factor for AIHP and that night workers may be at increased risk for developing liver injury with alcohol consumption.